Rapid plasmid replicon typing by real time PCR melting curve analysis - Boot, Maikel (BioMed Central, 2013)
BACKGROUND: Genes encoding Extended Spectrum Beta Lactamases are usually located on transferable plasmids. Each plasmid contains its own replication mechanism. Carattoli et al. developed an extended PCR-based replicon typing method to characterize and identify the replicons of the major plasmid incompatibility groups in Enterobacteriaceae. Based on this method, we designed a rapid approach with amplicon detection by real-time melting curve analysis. This method appeared to be fast, sensitive, less laborious, less prone to contamination and applicable in a routine laboratory environment. RESULTS: We successfully integrated the post-PCR analysis of the replicon typing into a closed system, which leads to a 10-fold increase in sensitivity compared to agarose gel visualization. Moreover, the use of crude lysates and SYBR-green saves a considerable amount of hands-on time without decreasing the sensitivity or specificity. CONCLUSIONS: This real-time melting curve replicon typing method appears to be fast, sensitive, less laborious, less prone to contamination and applicable in a routine laboratory environment.